(3TaGA GdUOhQ aj RjGQI GdTGgO hGdbHhQs - (3eQYj Hf jhSa Hf CHj HcQ Hf CMeO GdcQej GdebOSj GdMfHdi,J (B1033 (3g` s
(3ChdgG (B:s
(3bGd GdYHO GdabjQ Edi Gddg JYGdi eQYi Hf jhSa GdMfHdi GdebOSi hHYO abO CMHHJ Cf CVY HYV ahGFO dWjaI JJYdb HRjGQI GdeTGgO hGdbHhQ hbO LYdJgG YTQI CHhGH GdHGH GdChd ai RjGQI GdbHhQ s
(3BNQgG (B:s
(3bGd GdbGVi YjGV aeKd gPG hCTHGgg ef CehQ GdOfjG GdJi dG eONd ajgG dYde OjGfI hTZd faSg HgG GfJgi hGddg SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fbdJ Yf NW ef NW eDdags
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs